2020
DOI: 10.5603/gp.2020.0006
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal depression and anxiety in primiparous Polish mothers and fathers

Abstract: Objectives: Mood disturbances are the most prevalent mental health problems in expectant parents. The knowledge about the factors which increase the risk of perinatal depression is insufficient, especially in fathers. The aims of the present study were to estimate the prevalence and to compare mean levels of antenatal depression and anxiety as well as to examine the relationship between the risk for depression and anxiety in primiparous Polish parents.Material and methods: 250 parental couples participating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In 6 studies (26%), data were presented for the antenatal period. [23][24][25][26][27][28] Two studies reported couple-level data for both antenatal and postnatal time points. 25,27 All studies were performed in high-income countries (according to World Bank gross national income per capita criteria), 29 apart from 1 that was performed in Brazil.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In 6 studies (26%), data were presented for the antenatal period. [23][24][25][26][27][28] Two studies reported couple-level data for both antenatal and postnatal time points. 25,27 All studies were performed in high-income countries (according to World Bank gross national income per capita criteria), 29 apart from 1 that was performed in Brazil.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…[17][18][19][20][21][22] Sample size varied from 51 couples to more than 12 000 couples. [16][17][18][19][20][21][22][23][24][25] Most studies assessed postnatal depression. In 6 studies (26%), data were presented for the antenatal period.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 157 first-time couples, perinatal mood and relationship satisfaction were the strongest predictors of postnatal depression among fathers (Matthey et al 2000 ). Perinatal depression was higher among Finnish men with lower education (Korja et al 2018 ), among New Zealand men with high self-reported stress and lower physical health (Underwood et al 2017 ), and higher in Polish men with high anxiety (Kiepura and Kmita 2020 ). Sleep patterns are also strong predictors of paternal declines in mental health, whereby men who sleep 5–6 h per night are at highest risk of AND and PND (Krueger and Friedman 2009 ; Wynter et al 2020 ).…”
mentioning
confidence: 99%